Notary Responsibility For The Truth Of Data In Agreement Making In Financial Institutions Based On Sharia In Indonesia - Emy Lestari Langobelen (Sultan Agung Notary Law Review, 2020)
Notary is a public official appointed by the government to assist the general public in making agreements that exist or arise in society. The need for written agreements to be made before a notary is to guarantee legal certainty and to fulfill strong law of evidence for the parties who enter into the agreement. It is the need for written proof that calls for the importance of this notary institution. Notary is a profession so that the Notary profession is a noble profession (nobile offecium). In Act No. 30 of 2004 in conjunction with Act No. 12 of 2014 concerning the position of Notary Public, Article 1 paragraph (1) states ``Notaries are public officials who are authorized to make authentic deeds and have other powers as referred to in this Law. or based on other laws.''